Suboptimal adherence to doxycycline and treatment outcomes among men with non-gonococcal urethritis: a prospective cohort study. (8th October 2013) - Khosropour, Christine M; Manhart, Lisa E; Colombara, Danny V; Gillespie, Catherine W; Lowens, M Sylvan; Totten, Patricia A; Golden, Matthew R; Simoni, Jane
Abstract : Objective: Doxycycline, one of two recommended therapies for non-gonococcal urethritis (NGU), consists of a 7-day course of therapy (100 mg BID). Since suboptimal adherence may contribute to poor treatment outcomes, we examined the association between self-reported imperfect adherence to doxycycline and clinical and microbiologic failure among men with NGU. Methods: Men aged ≥16 years with NGU attending a Seattle, WA, sexually transmitted diseases clinic were enrolled in a double-blind, parallel-group superiority trial from January 2007 to July 2011. Men were randomised to active doxycycline/placebo azithromycin or placebo doxycycline/active azithromycin. Imperfect adherence was defined as missing ≥1 dose in 7 days. Urine was tested for Chlamydia trachomatis (CT), Mycoplasma genitalium (MG), and Ureaplasma urealyticum -biovar 2 (UU-2) using nucleic acid amplification tests. Clinical failure (symptoms and ≥5 PMNs/HPF or discharge) and microbiologic failure (positive tests for CT, MG, and/or UU-2) were determined after 3 weeks. Results: 184 men with NGU were randomised to active doxycycline and provided data on adherence. Baseline prevalence of CT, MG and UU-2 was 26%, 13% and 27%, respectively. 28% of men reported imperfect adherence, and this was associated with microbiologic failure among men with CT (aRR=9.33; 95% CI 1.00 to 89.2) and UU-2 (aRR=3.08; 95% CI 1.31 to 7.26) but not MG. Imperfect adherence was not significantly associated with clinical failure overall or for any specific pathogens, but it was more common among imperfectly adherent men with CT (aRR=2.63; 0.93–7.41, p=0.07). Conclusions: Adherence may be important for microbiologic cure of select pathogens. Factors other than adherence should be considered for CT-negative men with persistent NGU.